2007
DOI: 10.1111/j.1365-2249.2007.03362.x
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight proteins of outer membrane of Salmonella typhimurium are immunogenic in Salmonella induced reactive arthritis revealed by proteomics

Abstract: SummaryIn patients with reactive arthritis (ReA)/undifferentiated spondyloarthropathy (uSpA), synovial fluid mononuclear cells (SFMC) show proliferation to bacterial antigens that trigger ReA, i.e. Chlamydia, Yersinia, Campylobactor, Shigella and Salmonella species. We have shown previously that SFMC proliferate significantly to outer membrane proteins of S typhimurium in Salmonella induced ReA. In the present study we characterized the immunoreactive fractions of outer membrane protein (Omp) of S typhimurium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Like OmpA, OmpW is immunogenic in Salmonella induced reactive arthritis; all fractions producing immunoproliferative responses contained OmpA and OmpW [46]. Sixty percent of Celiac disease patients were seropositive for Bacterioides OmpW antibodies [67], and serum levels decreased significantly when patents were on a gluten free diet [68].…”
Section: Ompw Familymentioning
confidence: 98%
See 1 more Smart Citation
“…Like OmpA, OmpW is immunogenic in Salmonella induced reactive arthritis; all fractions producing immunoproliferative responses contained OmpA and OmpW [46]. Sixty percent of Celiac disease patients were seropositive for Bacterioides OmpW antibodies [67], and serum levels decreased significantly when patents were on a gluten free diet [68].…”
Section: Ompw Familymentioning
confidence: 98%
“…OmpA is among a number of low molecular weight immunogenic proteins in Salmonella-induced reactive arthritis [46]. In typhoid fever, the immune response is also directed against porins and OmpA [47][48][49].…”
Section: Immunoprophylatic Potential Of Ompamentioning
confidence: 99%
“…OmpW proteins have been associated with the attachment of Vibrio alginolyticus; OmpWdeficient mutants showed a 10-fold reduction in mouse colonization (50). OmpW was recently identified as being related to the immune response in inflammatory bowel disease associated with an oral pathogen, Porphyromonas gingivalis (51), and is immunogenic in Salmonella-induced reactive arthritis (52). We have recently shown that immunization of mice with OmpW also protects against B. pseudomallei infection (W. T. Casey, N. Spink, F. Cia, C. Collins, M. Romano, R. Berisio, G. J. Bancroft, and S. McClean, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%
“…Components of triggering bacteria including nucleic acids and protein have been identified in the synovium and in circulatory monocytes of patients diagnosed with ReA [14]. It is not clear how and in what form the bacterial components reach the joint and whether there are viable bacteria in the joint.…”
Section: Pathophysiologymentioning
confidence: 99%